The Mediating Role of Organizational Learning and Supply Chain Management Practices: Influence of Knowledge Management Capabilities on Organizational Performance - Sinta Putri Anggraini (Universitas Muhammadiyah Purwokerto, 2025)
The increasing complexity of business environments demands that organizations, especially MSMEs, develop their internal capabilities to remain competitive and sustainable. This study aims to analyze the effect of knowledge management capability on organizational performance, mediated by organizational learning and supply chain management practices. A quantitative approach was employed using Structural Equation Modeling (SEM), with data collected through questionnaires from 97 furniture MSME actors in Yogyakarta. The results show that knowledge management capability does not directly enhance organizational performance but has a positive effect through organizational learning as a mediator. In contrast, supply chain management practices do not have a positive impact on organizational performance, either directly or as a mediator. These findings highlight the importance of organizational learning in improving the performance of furniture MSMEs in Yogyakarta.